(untitled) (Heritage, 2025)
The review presents Trails of Ulysses: Echoes of James Joyce’s Work in Serbian Literature, a proceedings volume created to mark the centenary of Joyce’s novel, based on presentations at a roundtable held in June 2022. The publication was edited by Professor Zoran Paunović, a distinguished expert in Anglophone literature and the translator of Ulysses into Serbian. The volume features contributions from leading scholars in Serbian literature, each offering their insights into Joyce’s influence.